Balance Funds and SDGS in Riau Province: To What Extent Policies Support The Achievement of Sustainable Development Goals – An Approach Systematic Literature Review - Fendri Jaswir,; Sufian Hamim,; Rahyunir Rauf,; Gatot Wijayanto, (Proceeding International Conference on Social Sciences, 2026)
This conceptual paper aims to systematically examine the relationship between fiscal balance policies and the achievement of Sustainable Development Goals (SDGs) in Riau Province, Indonesia. Using a Systematic Literature Review (SLR) of 35 scholarly articles published between 2018 and 2025, this study identifies integration patterns between local fiscal policy and sustainable development agendas. The analysis focuses on three major fiscal transfer instruments—the General Allocation Fund (DAU), the Special Allocation Fund (DAK), and the Revenue Sharing Fund (DBH)—and their links to economic, social, and environmental SDG indicators. The findings reveal that the effectiveness of fiscal transfers in promoting SDG achievements in Riau remains limited due to weak local fiscal planning capacity, fragmented cross-sectoral coordination, and insufficient alignment between local budgeting and SDG targets. This study recommends strengthening the integration of fiscal and sustainable development policies through transparent, data-driven, and results-oriented governance.